2010
DOI: 10.1128/iai.01397-09
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Stable Enterotoxin of EnterotoxigenicEscherichia colias a Vaccine Target

Abstract: 5Enterotoxigenic Escherichia coli (ETEC) is responsible for 280 million to 400 million episodes of diarrhea and about 380,000 deaths annually. Epidemiological data suggest that ETEC strains which secrete heat-stable toxin (ST), alone or in combination with heat-labile toxin (LT), induce the most severe disease among children in developing countries. This makes ST an attractive target for inclusion in an ETEC vaccine. ST is released upon colonization of the small intestine and activates the guanylate cyclase C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 74 publications
3
72
0
Order By: Relevance
“…This is important because ST is poorly antigenic or nonantigenic, shares epitope homology with the human endogenous peptides of the guanylin family, and has yet to be incorporated into a vaccine construct; however, efforts of with ST-toxoid fusions are actively being developed. 19,20 Our finding that ST as the most common ETEC toxin is in agreement with a systematic review carried out by Isidean and others 6 In their study among travelers acquiring diarrhea in Latin America, the proportion of ETEC expressing ST was 67% and for travelers in south Asia it was 56%. In our study, we found that 56% of ETEC identified were ST-producing strains among travelers to Mexico, Guatemala, and India.…”
Section: Discussionsupporting
confidence: 77%
“…This is important because ST is poorly antigenic or nonantigenic, shares epitope homology with the human endogenous peptides of the guanylin family, and has yet to be incorporated into a vaccine construct; however, efforts of with ST-toxoid fusions are actively being developed. 19,20 Our finding that ST as the most common ETEC toxin is in agreement with a systematic review carried out by Isidean and others 6 In their study among travelers acquiring diarrhea in Latin America, the proportion of ETEC expressing ST was 67% and for travelers in south Asia it was 56%. In our study, we found that 56% of ETEC identified were ST-producing strains among travelers to Mexico, Guatemala, and India.…”
Section: Discussionsupporting
confidence: 77%
“…Given the fact the STa is poor immunogenic (<2000 Daltons) [5,6], hence the first step toward triggering an appropriate immune response against STa is to couple it to an appropriate carrier. Several strategies have been investigated to make STa immunogenic either through chemical conjugation [6,[31][32][33] or recombinant fusion protein [7,[34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the development of a subtle vaccine against ETEC diarrhea is deemed necessary for both human and livestock health as well. However, STa presents a problematic antigen owing to its poor immunogenic nature caused by its small molecular weight which is less than 2 KDa [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…STh is an 18-mer peptide and is non-immunogenic when administered alone (15). Previous reports have indicated that when chemically coupled or genetically fused to a protein carrier the ST-protein conjugate is able to elicit anti-ST antibody, and in some instances, the antiserum is able to neutralize the toxic activity of ST.…”
Section: Antibody Responses Elicited By Modular Vaccine Candidate Basmentioning
confidence: 99%
“…This toxin is secreted by pathogenic strains of E. coli and causes diarrhea especially among children in developing countries. Antibodies directed to ST can neutralize the toxin and prevent the occurrence of diarrhea (15), although ST itself is not immunogenic. (ii) Gonadotrophin-releasing hormone also known as luteinizing hormone-releasing hormone (LHRH) with the sequence HWSYGLRPG is secreted by the hypothalamus and initiates a cascade of endocrine events that govern reproduction.…”
Section: Synthetic Lipopeptides Containing S-[23-bis(palmitoyloxy)-pmentioning
confidence: 99%